(untitled) (Advances in Civil and Architectural Engineering, 2021)
The last three decades have seen increasing applications of fiber-reinforced polymer materials in structural engineering because of their many advantages over traditional strengthening and reinforcing materials. On the other hand, soft computing approaches have recently been widely used to model human activity in many areas of civil engineering applications. This paper presents the use of genetic expression programming as a tool to predict the ultimate axial strain of fiber-reinforced polymer-confined concrete. A large experimental data set (219) of these tests is collected from published literature. The prediction of the proposed new genetic expression programming-based model was compared with the results obtained using the existing analytical equations proposed in the current literature. In this paper, attempts were made to present a complete review of genetic expression programming in structural engineering. Good agreement between the experimental data and predicted results is obtained.